Clinical Presentations and Surgical Features of Morgagni Hernia in Adults: A Retrospective Study - Parviz Mardani; Farzad Dalfardi; Saman Bahmani; Rahem Rahmati; Fatemeh Zarimeidani; Bizhan Ziaian; Armin Amirian; Masoud Vafabin; Reza Shahriarirad (Health Science Reports)
ABSTRACT Background and Aims Morgagni hernias are rare congenital diaphragmatic defects that can lead to bowel obstruction and incarceration if not repaired. While this disease typically manifests as respiratory distress, frequent respiratory infections, and infant growth failure, it can sometimes be accidentally discovered in adulthood through cross‐sectional imaging. We aimed to report our experience managing this entity during 20 years at our referral center. Methods A retrospective chart review was performed of adult patients diagnosed with Morgagni diaphragmatic hernia who underwent surgery at Shiraz University of Medical Sciences in two main referral hospitals between 2002 and 2022. Patients' demographic and clinical data, including surgical features and hospitalization, course were extracted and subsequently analyzed. Results Seventeen patients, including three men and 14 women, with an age range of 26 to 92 years (average age 61.5 years), were diagnosed with Morgagni diaphragmatic hernia. Three patients had left‐sided hernias, and 14 had right‐sided hernias. The most common clinical manifestations were shortness of breath and abdominal pain. The most commonly herniated contents were the omentum and colon. All patients underwent laparotomy, and the hernia sac was removed in 11 patients. Conclusions Morgagni is a rare congenital diaphragmatic hernia usually diagnosed incidentally. Laparoscopic repair has high success rates and is a viable option for patients with this pathology.